PERAN ORANG TUA DALAM MENGATASI PERILAKU MEROKOK REMAJA DI JORONG RAMBAHAN NAGARI TANJUNG BETUNG KABUPATEN PASAMAN - Yanita, Wilda; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
Based on the phenomenon, the researcher found that there were some parents who did not pay attention to the adolescent boys who have smoking behavior, as well as they were not seriously in controlling the time, give affection and attention to them. So, from the events researcher interested to raise issue about the research: The role of parents in avoiding smoking behavior for adolescent boys in Jorong Rambahan Nagari Tanjung Betung Kabupaten Pasaman. The purpose of the research is to describe the role of parents: 1) Providing a natural affection to adolescents. 2) Providing supervision toward adolescentsâ association. 3) Providing adequate attention toward adolescentsâ requirement. This research was quantitative descriptive research, the population of this research was all of parents who have adolescent boys which amount 45 people. In selecting sample the researcher used total sampling Technique. The instrument of this reserach was used questionnaire method, meanwhile in analyzing the data the researcher used percentage technique. The results of this research is to reveal that the role of parents in controlling adolescentsâ smoking behavior: 1) Providing a natural affection in unfavorable category which 55.6 %. 2) Providing supervision toward adolescentsâ association in unfavorable category which 60 %. 3) Providing adequate attention toward adolescentsâ requirement in unfavorable category which 77.8 %. Based on the results of the research, the researcher suggests to parents who have adolescent boys with smoking behavior, the parents should give more attention and make time for adolescent. If all of that did not achieve they will seek his own pleasure outside the home, it wiil make adolescents were trapped in smoking behavior.